O ESPECTRO DO VERMELHO : UMA LEITURA TEOLÓGICA DO SOCIALISMO NO PARTIDO DOS TRABALHADORES A PARTIR DE PAUL TILLICH E DE ENRIQUE DUSSEL. - Santos, Jorge Pinheiro dos (2006)
With the foundation of the Workers Party (PT), the dream of the new Brazilian Left of a socialist future for the country began to become a reality. However, when this phenomenon was closely examined, it became clear that the PT had broken with the standards of a working-class party, not only for being an amalgam of tendenc ies, but also by a strong Christian presence. Hence, the question arose: what party is this? Starting from the theological analyses developed by Paul Tillich, I sought in this dissertation to build a new road for explaining the PT s appearance and the importance of social Christian thought in its creation and development. As theoretical references, I used two authors, Paul Tillich and Enrique Dussel. Socialist texts and Tillich s concepts of theology of culture, as well as approaches concerning infrastructural religion and the religious factor in the Latin- American revolutionary process developed by Enrique Dussel, guided my methodological reading. Thus, the research project was socialism in the Workers Party, from a theological approach; that is why the dissertation shows the importance of Theology in the interdisciplinary debate on socialism in the PT. All in all, including Theology in the critical analysis of developing the socialist thought in the PT, without denying the importance of interdisciplinary dialogues, broadens the horizon for understanding studies on politics, Christianity and socialism in Brazil, and also shows the importance of a comparative approach, represented by the presence of Theology in the discussion on politics and socialism. The primary and qualitative bibliographical research started from official documents of PT s meetings and congresses, as well as articles, editorials and interviews published by the PT press and nonpartisan press.